Palatability assessment of presribed diets on domesrtic short hair cats - Ilias, Nazhan; Hakim Zaki, Ahmad Harris; Awang Junaidi, Awang Hazmi; Lau, Seng Fong; Saufi, Ikhwan; Ajat, Mokrish (Veterinary World, 2022)
Background and Aim: The value of the pet food industry, which is majorly the prescribed diet, exponentially increased over the years due to increased awareness among pet owners to provide a healthy lifestyle for their pets. However, several factors such as aroma, flavor, texture, and shape of prescribed diets greatly influenced the palatability in cats. Therefore, this study aimed to determine the palatability of the prescribed diet for domestic shorthair (DSH) cats. Materials and Methods: The two-bowl method was employed to determine the palatability of prescribed diets on five DSH cats for 6 days. Furthermore, the four types of prescribed diet assessed in this study were struvite, renal, hypersensitivity, and intestinal. Furthermore, the pet food palatability was analyzed using “First Approached,” “First Consumed,” “Total Consumption,” and “Intake ratios.” Results: Our findings revealed that “Total Consumption” and “Intake Ratios” were significantly different in struvite, renal, and intestinal diets compared to the hypersensitivity diet. In addition, this result indicates that the hypersensitivity diet is the most unpalatable compared with other diets. Conclusion: A detailed investigation of the diet ingredients showed that a hypersensitivity diet lacks herbs and spices than the other diets. Therefore, these ingredients lacking in the hypersensitivity diet influence the palatability of pet foods.